Influence of mold temperature and process time on the degree of cure of epoxy-based materials for thermoset injection molding and prepreg compression molding - Deringer, Tim; Gröschel, Christian; Drummer, Dietmar (Journal of Polymer Engineering, 2017)

In situ curing and bonding of epoxy prepregs in epoxy thermoset injection molding - Deringer, Tim; Drummer, Dietmar (International Journal of Advanced Manufacturing Technology, 2021)
In this study, epoxy molding compounds are combined with fast-curing epoxy prepregs in thermoset injection molding using a new integrative process. The combination is carried out under the varied parameters of mold temperatures and curing times, which are dominant factors in thermoset processing. The focus of the investigations is the bond strength in the interface resulting from these parameters, as the interface is known as the weak point of hybrid components. To identify causes for possible increases and decreases of the bond strength, additional rheological and thermoanalytical analyses are done under near-process conditions. The influence of prepreg pre-crosslinking, a function of the mold temperature, is also described by means of additional tests in which specific pre-crosslinking of the prepreg is adjusted by the temperature storage and then functionalized in integrative process combination. The aim of the study is to identify and understand initial process limits for the integrative process combination for a potential process window.
CRIS-Team WoS Importer:2021-08-27

Integrative manufacturing of thermoset injection molding components with continous fiber-reinforcement - Deringer, Tim; Kleffel, Tobias; Drummer, Dietmar (Zeitschrift Kunststofftechnik, 2019)

Reduction of overmolding of Thermoset In-Mould produced hybrid components - Deringer, Tim; Drummer, Dietmar (Proceedings of SPE ANTEC 2019, 2019)

The influence of mold temperature on thermoset in-mold forming - Deringer, Tim; Drummer, Dietmar (Journal of Polymer Engineering, 2020)